2018
DOI: 10.1016/j.pestbp.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A new herbicidal site of action: Cinmethylin binds to acyl-ACP thioesterase and inhibits plant fatty acid biosynthesis

Abstract: The prevalent occurrence of herbicide resistant weeds increases the necessity for new site of action herbicides for effective control as well as to relax selection pressure on the known sites of action. As a consequence, interest increased in the unexploited molecule cinmethylin as a new solution for the control of weedy grasses in cereals. Therefore, the mechanism of action of cinmethylin was reevaluated. We applied the chemoproteomic approach cellular Target Profiling™ from Evotec to identify the cinmethylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
141
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(143 citation statements)
references
References 34 publications
1
141
0
1
Order By: Relevance
“…First, it was clarified that the site of action of the herbicide cinmethylin, whose registration has expired (in Japan), is fatty acid thioesterase (FAT). 88) The second herbicide is cyclopyrimorate. It has been reported that the site of action of this new herbicide, discovered by Mitsui Chemicals Agro and registered in Japan in September 2019, is the homogentisate solanesyltransferase (HST).…”
Section: After 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…First, it was clarified that the site of action of the herbicide cinmethylin, whose registration has expired (in Japan), is fatty acid thioesterase (FAT). 88) The second herbicide is cyclopyrimorate. It has been reported that the site of action of this new herbicide, discovered by Mitsui Chemicals Agro and registered in Japan in September 2019, is the homogentisate solanesyltransferase (HST).…”
Section: After 2018mentioning
confidence: 99%
“…It has recently been revealed by BASF scientists that cinmethylin binds to fatty acid thioesterase (FTA), a new herbicidal site of action, and inhibits plant fatty acid biosynthesis. 88) BASF has recently developed cinmethylin (Luximax, trade name: Luximo TM) ) as an herbicide to control key grasses in cereals. It demonstrates excellent efficacy against blackgrass and ryegrass, including resistant biotypes, while maintaining crop selec-…”
Section: Vlcfae Inhibitorsmentioning
confidence: 99%
“…Discovery of the MOA of an old herbicide cannot be considered as the entry of a new MOA into the market, but knowing the MOA may help with herbicide resistance management. Examples of the discovery of MOAs for older herbicides are the finding that endothall is a serine/threonine protein phosphatase inhibitor and that cinmethylin inhibits fatty acid thioesterases . Herbicides with truly new MOAs are badly needed for herbicide resistance management.…”
Section: Introductionmentioning
confidence: 99%
“…Also, cinmethylin targets the protein extracts of Lemna paucicostata Hegelm. that bind and validate FAT (fatty acid thioesterase) inhibition as a new site of action, different from other lipid biosynthesis inhibitors [23].Besides, researchers have been exploiting the processes of isolating new bioactive compounds from higher plants, especially from medicinal plants [24]. However, several novel bioactive substances that can lead to the identification of new herbicide sites of action that remain untapped in medicinal plants [25].…”
mentioning
confidence: 99%
“…Also, cinmethylin targets the protein extracts of Lemna paucicostata Hegelm. that bind and validate FAT (fatty acid thioesterase) inhibition as a new site of action, different from other lipid biosynthesis inhibitors [23].…”
mentioning
confidence: 99%